PENGARUH PEMBERIAN TEPUNG UMBI GEMBILI TERHADAP PANJANG USUS HALUS PUYUH - Setyaningrum, Sri; Sari Siregar, Dini Julia; Warisman, Warisman (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
The purpose of this study was to determine the effect of gembili tuber flour on the length of the small intestine of quail. This study was used 200 male quails aged 2 weeks. This study used a completely randomized design consist of 4 treatments with 5 replications. Treatments of the study included T0: control (0% gembili tuber flour), T1: basal diet + 0.3% gembili tuber flour, T2: basal diet + 0.6% gembili tuber flour, T3: basal diet + 0.9% gembili tuber flour. The parameters of this study were the length of the duodenum, jejunum and ileum. The treatment of gembili tuber flour had no significant effect (p>0.05) on the length of the duodenum, jejunum and ileum of the quail. Based on the results of the study it was concluded that the administration of gembili tuber flour was not affected the length of the small intestine of quail.